Pengembangan Sumber Belajar Berbasis Blog pada Pembelajaran Matematika Kelas XI MIPA SMA Negeri 2 Padang - LOVADA SARI (Departemen Matematika, 2020)
The aim of deveopment of blog based learning resources on mathematics learning in eleventh grade of SMAN 2 Padang is to facilitate students learning mathematics materials by using their smartphones. They can access blog based learning resources wherever and whenever they want. Deveopment of blog based learning resources on mathematics learning in eleventh grade of SMAN 2 Padang applies ASSURE model. The procedures of ASSURE model[5]. By following its procedures, the result shows blog based learning resources get valid and practical. Therefore, blog based learning resources on mathematics learning in eleventh grade can be applied in eleventh grade of senior high schools as mathematics learning resources. Keywords–Learning resources, Blog, Mathematics, ASSURE